Interaction of the repressors Nrg1 and Nrg2 with the Snf1 protein kinase in Saccharomyces cerevisiae. - Vyas, V K (2001)
The Snf1 protein kinase is essential for the transcription of glucose-repressed genes in Saccharomyces cerevisiae. We identified Nrg2 as a protein that interacts with Snf1 in the two-hybrid system. Nrg2 is a C(2)H(2) zinc-finger protein that is homologous to Nrg1, a repressor of the glucose- and Snf1-regulated STA1 (glucoamylase) gene. Snf1 also interacts with Nrg1 in the two-hybrid system and co-immunoprecipitates with both Nrg1 and Nrg2 from cell extracts. A LexA fusion to Nrg2 represses transcription from a promoter containing LexA binding sites, indicating that Nrg2 also functions as a repressor. An Nrg1 fusion to green fluorescent protein is localized to the nucleus, and this localization is not regulated by carbon source. Finally, we show that VP16 fusions to Nrg1 and Nrg2 allow low-level expression of SUC2 in glucose-grown cells, and we present evidence that Nrg1 and Nrg2 contribute to glucose repression of the DOG2 gene. These results suggest that Nrg1 and Nrg2 are direct or indirect targets of the Snf1 kinase and function in glucose repression of a subset of Snf1-regulated genes.